0107 Altered Metabolites In The Human Plasma Metabolome During Insufficient Sleep Are Associated With Reduced Insulin Sensitivity. (12th April 2019) - Depner, Christopher M; Melanson, Edward; Eckel, Robert; Snell-Bergeon, Janet; Perreault, Leigh; Bergman, Bryan; Higgins, Janine; Cruickshank-Quinn, Charmion; Quinn, Kevin; Reisdorph, chole; Wright, Kenneth
Abstract: Introduction: Our previous findings show insufficient sleep reduces insulin sensitivity (SI ) and thereby increases diabetes risk. Yet, the mechanisms underlying reduced SI during insufficient sleep are not fully understood. To identify potential biochemical mechanisms underlying reduced SI associated with insufficient sleep, we investigated the human plasma metabolome during adequate and insufficient sleep using untargeted metabolomics. Methods: Fourteen healthy adults (7M/7F; aged 25.2±4.7yr; BMI 22.5±2.0kg/m 2 [mean±SD]) completed an in-laboratory study consisting of three baseline days with 9h sleep opportunities/night followed by 10 days of insufficient sleep with 5h sleep opportunities/night. SI was assessed at baseline and on study day 12 (after 8 days insufficient sleep) using hyperinsulinemic/euglycemic clamps. Fasted plasma samples collected 1h after scheduled waketime on study days 3 (baseline) and 11 (insufficient sleep) were analyzed by untargeted LC/MS in aqueous and lipid fractions. Elastic net regularized regression identified associations between changes in plasma metabolites and SI . Results: After controlling for change in body-weight, SI decreased ( P <0.05) ~13% during insufficient sleep versus baseline. After filtering, 3, 592 metabolites were detected. The elastic net model identified 13 metabolites associated with SI during insufficient sleep with an R-squared of 0.93 ( P <0.001) based on leave-one-out cross-validation. Five metabolites in the model are tentatively identified as follows: a monoglycosylceramide, phosphatidylcholine-42:8, malvidin3-glucoside-4-vinylphenol (an anthocyanidin), 1alpha, 25-dihydroxy-2beta-5-hydroxypentoxyvitaminD3 (vitamin-D derivative), and PS(O-40:2) (a plasmalogen). Conclusion: Using discovery metabolomics we identified 13 metabolites associated with reduced SI during insufficient sleep. Increases in monoglycosylceramides are known to decrease SI, supporting our current findings. Decreases in overall phosphatidylcholine levels can disrupt cell-membrane integrity and are linked with metabolic disease. Links between the other identified metabolites and SI are less clear. Yet, these metabolites are all linked with oxidative stress suggesting oxidative stress during insufficient sleep may link these metabolites with SI . Collectively, our findings suggest altered lipid metabolism during insufficient sleep may contribute to reduced SI . Further lipidomics studies are required to validate our current discovery based metabolomics findings. Support (If Any): NIH-R01HL085705, NIH-R01HL109706, NIH-R01HL132150, NIH-F32DK111161, and NIH-UL1TR000154; and Sleep Research Society Foundation 011-JP-16